PENGGUNAAN APLIKASI REKAP SURAT BERBASIS DESKTOP DI PMI KOTA MALANG - RIZA AKHSANI SETYO PRAYOGA; Asep Syahrul Mubarok (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
The Indonesian Red Cross is a humanitarian organization that focuses on collecting and collecting blood. The Indonesian Red Cross has a branch, one of which is in the city of Malang, where the administrative division has a problem regarding the recapitulation of correspondence. In this case, there is still a manual for recaping correspondence so that it is still difficult and confused if incoming and outgoing letters at the Indonesian Red Cross (PMI) Malang City are lost or accidentally wasted. So, we need an application that helps in recapitulating correspondence at the Indonesian Red Cross (PMI) Malang City. From this Desktop-Based Mail Recap Application, the Indonesian Red Cross (PMI) Malang City can save incoming and outgoing letters so that they will be stored by the application in the form of soft files. In addition, with the Desktop-Based Mail Recap Application, it helps in backing up data so that letter files can be stored neatly and the Indonesian Red Cross (PMI) Malang City can find mail files easily.